Palimpsest - Sjöblom, Lisa Wool-Rim (Drawn & Quarterly, 2019)
"Thousands of South Korean children were adopted around the world in the 1970s and 1980s. More than nine thousand found their new home in Sweden, including the cartoonist Lisa Wool-Rim Sjöblom, who was adopted when she was two years old. Throughout her childhood she struggled to fit into the homogenous Swedish culture and was continually told to suppress the innate desire to know her origins. "Be thankful," she was told; surely her life in Sweden was better than it would have been in Korea. Like many adoptees, Sjöblom learned to bury the feeling of abandonment. In Palimpsest, an emotionally charged memoir, Sjöblom's unaddressed feelings about her adoption come to a head when she is pregnant with her first child. When she discovers a document containing the names of her biological parents, she realizes her own history may not match up with the story she's been told her whole life: that she was an orphan without a background. As Sjöblom digs deeper into her own backstory, returning to Korea and the orphanage, she finds that the truth is much more complicated than the story she was told and struggled to believe. The sacred image of adoption as a humanitarian act that gives parents to orphans begins to unravel. Sjöblom's beautiful autumnal tones and clear-line style belie the complicated nature of this graphic memoir's vital central question: Who owns the story of an adoption?"--